A vanadium magnesium oxide cathode material coated with a conductive polymer and synergistically modified by oxygen vacancies, a preparation method therefor, and an application thereof
Patent Information
- Application Number
- CN202611165499.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明旨在解决现有钒酸镁正极材料在镁金属电池应用中,因Mg2+嵌入动力学缓慢、循环过程中结构退化与钒溶解严重,导致容量衰减快、倍率性能差、循环寿命短的技术难题,提供一种导电聚合物包覆与氧空位协同改性的钒酸镁正极材料及其一步水热制备方法,同步实现表面电导率提升、层间距扩大、本征电导率增强与结构稳定性优化
部分导电聚合物不仅包覆于钒酸镁材料表面,还可插入材料层间,从而进一步扩大层间距,由未包覆时的12.32 Å扩展至13.66 Å,为镁离子提供更宽的扩散通道,有利于降低离子迁移能垒,提升倍率性能。导电高分子包覆层均匀覆盖于钒酸镁纳米片表面,显著提升了材料的表面电子电导率,同时,该导电涂层可增强材料的结构稳定性,有效延长循环寿命。通过导电聚合物单体的氧化聚合过程,在钒酸镁基体中同步引入丰富的氧空位缺陷。氧空位与V4+/V5+混合价态协同作用,降低了静电相互作用及晶格应变,提升了Mg2+扩散动力学和材料的本征电子电导率。本发明采用一步水热法,合成工艺简单,原料廉价易得,无需多步复杂操作,具有良好的规模化生产前景。所制备的正极材料展现出优异的电化学性能,在200 mA g-1电流密度下循环300圈后,放电比容量仍高达191.2 mAh g-1,容量保持率接近100%;在500 mA g-1的高电流密度下循环450圈后,仍可保持175.9 mAh g-1的比容量;在-20℃的低温条件下,以20 mA g-1的电流密度循环150次后,仍可保持175.9 mAh g-1的比容量。
Smart Images

Figure CN122992028A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanomaterials and electrochemical energy storage technology, specifically relating to a conductive polymer-coated magnesium vanadate cathode material rich in oxygen vacancies, its preparation method, and its application in magnesium metal batteries. Background Technology
[0002] Lithium-ion batteries have been widely used in portable electronic devices and electric vehicles, but their development is limited by the low abundance of lithium resources in the Earth's crust (approximately 0.0017 wt%) and uneven geographical distribution, making it difficult to support the sustainable development of large-scale energy storage systems. Magnesium metal batteries, on the other hand, benefit from abundant magnesium resources and high volumetric capacity (3833 mAh). cm -3 With advantages such as no dendrite growth and excellent safety, Mg has become a next-generation electrochemical energy storage system with great development potential. However, Mg... 2+ High charge density leads to slow insertion / extraction kinetics in cathode materials, which easily induces lattice distortion and structural degradation, resulting in rapid capacity decay and significantly shortened cycle life.
[0003] Vanadium pentoxide (V₂O₅), as a typical layered oxide cathode material, has both high specific capacity and cost advantages. However, its initial interlayer spacing (approximately 4.38 Å) is small, making it difficult to accommodate Mg. 2+ Reversible intercalation is possible. Intercalation with water or organic molecules can increase interlayer spacing to some extent, but guest species are prone to detachment during cycling, leading to instability of the layered structure. In addition, vanadium-based oxides generally suffer from slow electron / ion diffusion kinetics, structural collapse during cycling, and dissolution of vanadium ions in the electrolyte, which severely restricts the realization of their high specific capacity advantage and the improvement of cycling stability.
[0004] Existing modification strategies include pre-intercalation of guest ions / molecules, compositing with conductive materials, constructing heterostructures, and introducing defect engineering. Among these, conductive polymer coating provides an external electron transport pathway, suppressing direct contact between vanadium and the electrolyte and alleviating vanadium dissolution. Simultaneously, during the oxidative polymerization of conductive polymer monomers, oxygen vacancies can be introduced into the vanadium-based matrix, improving the intrinsic electronic conductivity of the material. However, no method has yet achieved synergistic regulation of conductive polymer coating and oxygen vacancies in a one-step process, making it difficult to simultaneously address the multiple problems of slow ion diffusion, low electronic conductivity, and poor structural stability. Therefore, developing integrated synergistically modified high-performance vanadium-based magnesium battery cathode materials is of great significance. Summary of the Invention
[0005] This invention aims to solve the problem of existing magnesium vanadate cathode materials in magnesium metal battery applications, due to the presence of Mg... 2+The slow embedding kinetics, severe structural degradation and vanadium dissolution during cycling lead to rapid capacity decay, poor rate performance and short cycle life. This paper proposes a magnesium vanadate cathode material with conductive polymer coating and oxygen vacancy synergistic modification and its one-step hydrothermal preparation method, which simultaneously improves surface conductivity, expands interlayer spacing, enhances intrinsic conductivity and optimizes structural stability.
[0006] To achieve the above objectives, the present invention provides a magnesium vanadate cathode material with conductive polymer coating and oxygen vacancy synergistic modification. The cathode material is a magnesium vanadate nanosheet structure coated with conductive polymer, and the interior of the magnesium vanadate matrix is rich in oxygen vacancies. The conductive polymer is partially coated on the surface of magnesium vanadate and partially embedded between the magnesium vanadate layers. The mass percentage of conductive polymer in the cathode material is 13~25wt%.
[0007] Furthermore, the thickness of the surface coating layer of the conductive polymer is 3~4 nm; the interlayer spacing of the (001) crystal planes of magnesium vanadate is 13.60~13.66 Å.
[0008] Furthermore, the magnesium vanadate matrix contains V 4+ / V 5+ In the mixed valence state, oxygen vacancies are mainly located at the bridging oxygen sites of magnesium vanadate.
[0009] Furthermore, the conductive polymer is polymerized from one or more of 3,4-ethylenedioxythiophene (EDOT), aniline, pyrrole, thiophene, acetylene, and p-phenyleneethylene.
[0010] On the other hand, the present invention also provides a method for preparing a magnesium vanadate cathode material with conductive polymer coating and oxygen vacancy synergistic modification as described above, characterized by comprising the following steps: S1. Under water bath conditions, vanadium pentoxide powder and magnesium hydroxide powder are added to deionized water and stirred until homogeneous to obtain mixed solution A. S2. Add hydrogen peroxide solution to mixed solution A and stir thoroughly until the solution turns clear dark red to obtain vanadium-based precursor solution; S3. Add conductive polymer monomers to the vanadium-based precursor solution and sonicate at room temperature to obtain mixed solution B; S4. Transfer the mixed solution B to a polytetrafluoroethylene-lined reactor, seal it, and carry out a hydrothermal reaction. S5. After the reaction is complete, the mixture is allowed to cool naturally to room temperature. The product is collected by centrifugation, washed, and vacuum dried to obtain a magnesium vanadate cathode material with conductive polymer coating and oxygen vacancy synergistic modification.
[0011] Furthermore, in step S1, the water bath temperature is 65~75℃, the molar ratio of magnesium hydroxide to vanadium pentoxide is (0.8~1.2):2, and the stirring time is 0.5~1 h.
[0012] Furthermore, in step S2, the molar ratio of vanadium pentoxide to hydrogen peroxide is 1:(8~12), the stirring time is 0.5~1 h, and the amount of deionized water used is 70~80 mL per 4 mmol of vanadium pentoxide.
[0013] Furthermore, in step S3, the amount of 3,4-ethylenedioxythiophene monomer added is 0.15~0.20 mL per 1 mmol of vanadium pentoxide, and the ultrasonic treatment time is 2~3 h.
[0014] Furthermore, in step S4, the hydrothermal reaction temperature is 160~200℃ and the holding time is 34~38 h; in step S5, the product is washed with deionized water and ethanol respectively, and the vacuum drying temperature is 60~80℃ and the drying time is 14~18 h.
[0015] On the other hand, the present invention also provides an application of the magnesium vanadate cathode material as described above in magnesium metal batteries, wherein the magnesium vanadate cathode material is used as a cathode active material in magnesium metal button batteries or magnesium metal pouch batteries.
[0016] The beneficial effects of this invention are: Some conductive polymers not only coat the surface of magnesium vanadate materials but also insert into the interlayer space, further expanding the interlayer spacing from 12.32 Å in the uncoated state to 13.66 Å. This provides a wider diffusion channel for magnesium ions, which helps to reduce the ion migration energy barrier and improve rate performance. The conductive polymer coating layer uniformly covers the surface of magnesium vanadate nanosheets, significantly improving the surface electronic conductivity of the material. Simultaneously, this conductive coating enhances the structural stability of the material and effectively extends cycle life. Through the oxidative polymerization process of the conductive polymer monomers, abundant oxygen vacancy defects are simultaneously introduced into the magnesium vanadate matrix. Oxygen vacancies and V... 4+ / V 5+ The synergistic effect of mixed valence states reduces electrostatic interactions and lattice strain, thereby enhancing the Mg... 2+ Diffusion kinetics and intrinsic electronic conductivity of the material. This invention employs a one-step hydrothermal method, which is simple to synthesize, uses inexpensive and readily available raw materials, and eliminates the need for complex multi-step operations, showing good prospects for large-scale production. The prepared cathode material exhibits excellent electrochemical performance at 200 mA g. -1 After 300 cycles at the current density, the discharge specific capacity still reaches 191.2 mAh g⁻¹. -1 The capacity retention is close to 100%; at 500 mA g -1 After cycling at high current density for 450 cycles, it still maintains 175.9 mAh g⁻¹. -1 Specific capacity; at a low temperature of -20℃, at 20 mA g -1After 150 cycles, the current density still maintains 175.9 mAh g. -1 Specific capacity. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0018] Figure 1 These are the XRD patterns of the PEDOT-coated magnesium vanadate cathode material and the magnesium vanadate cathode prepared according to the embodiments of the present invention. Figure 2 These are (a) SEM images, (b) TEM images, and (c, d) HRTEM images of the PEDOT-coated magnesium vanadate cathode material described in the embodiments of the present invention. Figure 3 This is a comparison of Raman and FTIR of the PEDOT-coated magnesium vanadate cathode material and magnesium vanadate as described in the embodiments of the present invention. Figure 4 This is an XPS comparison image of the PEDOT-coated magnesium vanadate cathode material and magnesium vanadate as described in the embodiments of the present invention; Figure 5 This is a comparison chart of the cycle performance of the PEDOT-coated magnesium vanadate cathode material and the magnesium vanadate cathode described in the embodiments of the present invention; Figure 6 This is a comparison chart of the rate performance of the PEDOT-coated magnesium vanadate cathode material and the magnesium vanadate cathode described in the embodiments of the present invention. Detailed Implementation
[0019] The present invention will be described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the following embodiments.
[0020] Example 1 This invention provides a method for preparing and applying a magnesium vanadate cathode material coated with PEDOT conductive polymer and synergistically modified with oxygen vacancies, comprising the following steps: S1. Under the conditions of a water bath at 70℃, 0.7275 g (4 mmol) of V2O5 powder and 0.1162 g (2 mmol) of magnesium hydroxide powder were added to 75 mL of deionized water and stirred for 0.5 hours to obtain an orange-yellow mixed solution A. S2. Add 4.0 mL of hydrogen peroxide (H2O2>30 wt%) to mixed solution A, and continue stirring at 600 rpm for 1 hour under a water bath at 70℃ until the solution turns into a reddish-brown transparent liquid. S3. Slowly add 0.684 mL of EDOT monomer to the solution obtained in step S2, and then sonicate at room temperature for 2 hours to obtain mixed solution B; S4. Transfer the mixed solution B into a 100 mL polytetrafluoroethylene liner, seal it, and place it in a 180℃ high-temperature oven for 36 hours to carry out a hydrothermal reaction. S5. After the reaction is complete, the mixture is allowed to cool naturally to room temperature. The cotton-like precipitate is collected by centrifugation, washed three times each with deionized water and ethanol, and dried in a vacuum drying oven at 60°C for 18 hours to obtain dark green MVO@PEDOT powder.
[0021] It is foreseeable that magnesium metal battery cathode materials with excellent electrochemical performance can be obtained through the above methods.
[0022] Specifically, in step S1, the molar ratio of Mg(OH)2 to V2O5 is approximately 1:2, and the stirring time is 0.5 hours.
[0023] Specifically, in step S2, the molar ratio of V2O5 to H2O2 is approximately 1:10, and the stirring time is 1 hour.
[0024] Specifically, in step S3, the amount of EDOT monomer added is 0.684 mL (approximately 6.4 mmol), and each 1 mmol V2O5 corresponds to approximately 0.171 mLEDOT.
[0025] Specifically, in step S4, the hydrothermal reaction temperature is 180°C and the holding time is 36 hours.
[0026] This invention also provides the application of MVO@PEDOT cathode material in magnesium metal batteries, specifically including: The MVO@PEDOT powder, Ketjen Black, and PTFE binder prepared above were mixed evenly in ethanol at a mass ratio of 6:3:1, and rolled into a uniform film (for preparing electrode sheets), which was then vacuum dried overnight. A CR2016 coin cell was assembled using magnesium foil as the negative electrode, Mg(MPFB)2 as the electrolyte, and Whatman GF / D glass fiber as the separator.
[0027] The performance of the MVO@PEDOT material and the assembled battery prepared in Example 1 was tested, and the results are as follows: Figure 1-5 As shown.
[0028] Figure 1X-ray diffraction (XRD) patterns of PEDOT-coated magnesium vanadate storage material and magnesium vanadate are shown. It can be observed that the main diffraction peak positions of MVO@PEDOT and uncoated MVO are not significantly shifted, indicating that the PEDOT coating did not disrupt the basic crystal structure of magnesium vanadate. Notably, the interlayer spacing of the (001) crystal plane of MVO@PEDOT is 13.60 Å, significantly larger than the 12.32 Å of uncoated MVO, indicating that some PEDOT molecules have inserted into the interlayer space, further expanding the interlayer spacing.
[0029] Figure 2 TEM, SEM, and STEM results show that MVO@PEDOT exhibits a nano-stacked sheet-like morphology with a sheet length of approximately 1 μm. The PEDOT coating layer uniformly and completely covers the material surface with a thickness of approximately 3–4 nm. HRTEM images show a crystal plane spacing of 13.60 Å, corresponding to the (001) crystal plane, further confirming the embedding of PEDOT and the expansion of the interlayer spacing.
[0030] Figure 3 Magnesium vanadate (MVO) storage material coated with PEDOT and Raman and FTIR spectra of magnesium vanadate. Raman spectroscopy shows that MVO@PEDOT exhibits activity at approximately 1500 cm⁻¹. -1 Symmetric and asymmetric stretching vibration peaks at the C=C bond were observed, while these characteristic peaks were not observed in the uncoated MVO, indicating that EDOT had successfully polymerized into PEDOT and that its conjugated system had been extended. In the FTIR spectrum, MVO@PEDOT showed peaks at 1200–1500 cm⁻¹. -1 The presence of characteristic absorption peaks for COC bonds within the range further confirms the successful introduction of PEDOT. Furthermore, the oxygen signal attributable to bridging oxygen sites in MVO@PEDOT is significantly weakened, indicating that oxygen vacancies are primarily located at bridging oxygen sites.
[0031] Figure 4 XPS spectra of V 2p and O 1s for PEDOT-coated magnesium vanadate and magnesium vanadate cathode. V in MVO@PEDOT 4+ The proportion of oxygen vacancies and the concentration of oxygen vacancies are significantly higher than those in uncoated MVO, indicating that this invention successfully introduces oxygen vacancy defects into magnesium vanadate. The generation of oxygen vacancies leads to the transfer of some electrons to vanadium atoms, resulting in a decrease in the average valence state of vanadium in MVO@PEDOT compared to MVO.
[0032] Figure 5 Magnesium vanadate coated with PEDOT and magnesium vanadate cathode at 200 mA g -1 Cyclic performance comparison at current densities. At 200 mA g... -1At a current density of [value missing], after 300 stable cycles, the discharge specific capacity of the MVO@PEDOT cathode remains as high as 191.2 mAh g⁻¹. -1 The capacity retention is close to 100%. At 500 mA g... -1 At high current densities, it can still maintain 175.9 mAh g after cycling for more than 450 cycles. -1 The specific capacity. Furthermore, the assembled pouch cell has a specific capacity of 20 mA g. -1 After 50 cycles at the current density, the discharge specific capacity reaches as high as 289.75 mAh g. -1 It demonstrates good potential for practical application.
[0033] Figure 6 A comparison of the rate performance of PEDOT-coated magnesium vanadate and magnesium vanadate cathodes. MVO@PEDOT cathode at 800 mA g -1 Even at high current densities, the specific capacity remains close to 100 mAh g. -1 When the current density recovers to 100 mA g -1 At that time, the specific capacity can be restored to 300.65 mAh g. -1 In contrast, the uncoated MVO cathode at 800 mA g -1 It can only provide about 40.56mAh g. -1 The specific capacity was restored to 100 mA g. -1 The specific capacity is only 135.60 mAh g. -1 This fully demonstrates the excellent rate performance of the material of this invention.
[0034] In summary, the PEDOT-coated and oxygen-vacancy synergistically modified magnesium vanadate cathode material provided by this invention exhibits high reversible specific capacity, excellent rate performance, and ultra-long cycle life in magnesium metal batteries, and has broad application prospects in the fields of advanced magnesium batteries and flexible wearable electronic devices.
[0035] Example 2 The difference between this embodiment and Embodiment 1 is that the amount of EDOT monomer added in step S3 is changed to 0.342 mL, while the other steps and parameters are the same as in Embodiment 1.
[0036] Test results showed that the obtained MVO@PEDOT had a low PEDOT content (approximately 7.2 wt%) and a relatively low oxygen vacancy concentration. At 200 mA g... -1 After 60 cycles at the current density, the discharge specific capacity is only 109.2 mAh g. -1 ;at 500 mA g -1 After 55 cycles, the specific capacity decreased to 80.6 mAh g. -1The performance was significantly lower than that of Example 1. Analysis suggests that the excessively low PEDOT content and oxygen vacancy concentration were insufficient to adequately improve the electronic conductivity and structural stability of the material.
[0037] Example 3 The difference between this embodiment and Example 1 is that the amount of EDOT monomer added in step S3 is changed to 1.368 mL, while the other steps and parameters are the same as in Example 1.
[0038] Test results showed that the obtained MVO@PEDOT had a high PEDOT content (approximately 32.8 wt%), and the oxygen vacancy concentration also increased accordingly. However, the excessively high PEDOT addition led to V 5+ Over-reduction to V 4+ EPR testing showed that this material had the highest oxygen vacancy concentration. (At 200 mA g) -1 At the current density, the initial discharge specific capacity is only 102.4 mAh g⁻¹. -1 ;at 500 mA g -1 After 170 cycles, the specific capacity is below 50 mAh g. -1 Analysis suggests that excessively high PEDOT content and oxygen vacancy concentration actually compromise the material's structural stability, leading to deterioration in electrochemical performance.
[0039] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A conductive polymer-coated and oxygen-vacancy synergistically modified magnesium vanadate cathode material, characterized in that, The cathode material is a magnesium vanadate nanosheet structure coated with a conductive polymer, and the interior of the magnesium vanadate matrix is rich in oxygen vacancies; the conductive polymer is partially coated on the surface of magnesium vanadate and partially embedded between the magnesium vanadate layers; the mass percentage of the conductive polymer in the cathode material is 13~25wt%.
2. The magnesium vanadate cathode material according to claim 1, characterized in that, The thickness of the surface coating layer of the conductive polymer is 3~4 nm; the interlayer spacing of the (001) crystal planes of magnesium vanadate is 13.60~13.66 Å.
3. The magnesium vanadate cathode material according to claim 1, characterized in that, V is present in the magnesium vanadate matrix. 4+ / V 5+ In the mixed valence state, oxygen vacancies are mainly located at the bridging oxygen sites of magnesium vanadate.
4. The magnesium vanadate cathode material according to claim 1, characterized in that, The conductive polymer is polymerized from one or more of 3,4-ethylenedioxythiophene (EDOT), aniline, pyrrole, thiophene, acetylene, and p-phenyleneethylene.
5. A method for preparing a magnesium vanadate cathode material with conductive polymer coating and oxygen vacancy synergistic modification as described in any one of claims 1 to 4, characterized in that, Includes the following steps: S1. Under water bath conditions, vanadium pentoxide powder and magnesium hydroxide powder are added to deionized water and stirred until homogeneous to obtain mixed solution A. S2. Add hydrogen peroxide solution to mixed solution A and stir thoroughly until the solution turns clear dark red to obtain vanadium-based precursor solution; S3. Add conductive polymer monomers to the vanadium-based precursor solution and sonicate at room temperature to obtain mixed solution B; S4. Transfer the mixed solution B to a polytetrafluoroethylene-lined reactor, seal it, and carry out a hydrothermal reaction. S5. After the reaction is complete, the mixture is allowed to cool naturally to room temperature. The product is collected by centrifugation, washed, and vacuum dried to obtain a magnesium vanadate cathode material with conductive polymer coating and oxygen vacancy synergistic modification.
6. The preparation method according to claim 5, characterized in that, In step S1, the water bath temperature is 65~75℃, the molar ratio of magnesium hydroxide to vanadium pentoxide is (0.8~1.2):2, and the stirring time is 0.5~1 h.
7. The preparation method according to claim 5, characterized in that, In step S2, the molar ratio of vanadium pentoxide to hydrogen peroxide is 1:(8~12), the stirring time is 0.5~1 h, and the amount of deionized water used is 70~80 mL per 4 mmol of vanadium pentoxide.
8. The preparation method according to claim 5, characterized in that, In step S3, the amount of 3,4-ethylenedioxythiophene monomer added is 0.15~0.20 mL per 1 mmol of vanadium pentoxide, and the ultrasonic treatment time is 2~3 h.
9. The preparation method according to claim 5, characterized in that, In step S4, the hydrothermal reaction temperature is 160~200℃ and the holding time is 34~38 h; in step S5, the product is washed with deionized water and ethanol respectively, and the vacuum drying temperature is 60~80℃ and the drying time is 14~18 h.
10. The application of a magnesium vanadate cathode material as described in any one of claims 1 to 4 in a magnesium metal battery, characterized in that, The magnesium vanadate cathode material is used as a cathode active material in magnesium metal button batteries or magnesium metal pouch batteries.